The Role of KDM2B and EZH2 in Regulating the Stemness in Colorectal Cancer Through the PI3K/AKT Pathway - Sanches, Jaceline Gisliane Pires; Song, Bo; Zhang, Qingqing; Cui, Xinye; Yabasin, Iddrisu Baba; Ntim, Michael; Li, Xinlong; He, Jiabei; Zhang, Yao; Mao, Jun; Lu, Ying; Li, Lianhong (Frontiers in Oncology, 2021)
Background: The incidence of colorectal cancer (CRC) has been increasing worldwide in recent years. Targeting cancer stem cells (CSCs) in CRC remains a difficult challenge. KDM2B and EZH2 play important role in the maintenance of CSC self-renewal capacity and tumorigenic ability, however, the biological functions of those genes in colorectal cancer remain unclear. In this study, we aimed to define the contribution of KDM2B expression in colorectal cancer features and the relationship between KDM2B and EZH2 influence in colorectal cancer stem cell. Methods: The expression of KDM2B and EZH2 in colorectal cancer specimens and colorectal cancer cell lines were analyzed by immunohistochemistry, western blot and immunofluorescence. The underlying mechanisms of altered KDM2B and EZH2 expression and their impact on CRC biologic feactures and CRC stemness were investigated. Results: KDM2B gene was highly expressed in CRC tissues and its overexpression positively correlated with tumor stages and TNM classification. The downregulation of KDM2B retarded cell proliferation, induced DNA damage, reduced spheroid formation and decreased CRC stem cell makers CD44, CD133, ALDH-1. Moreover, the downregulation of KDM2B decreased EZH2 expression and both regulated cell migration, invasion and stemness in CRC cell line. Additionally, the interaction between KDM2B and EZH2 significantly increased PI3K/AKT pathway components including AKT and PI3K. The high expression of KDM2B was positively correlated with EZH2 in CRC tissue. Conclusion: This study shows that the downregulation of KDM2B and EZH2 can regulate CRC cell stemness and their interaction may serve as a novel prognostic marker and therapeutic target for patients with CRC.